In Vitro Effects of Lipids on Fibrinolysis - Chopin, Suzzette F.; Beard, E Letitia (Thrombosis and Haemostasis, 1973)
The effect of suspensions of corn oil, butter, cholesterol, and beta lipoprotein in concentrations in the range of normal blood lipid levels on the ability of lytic agents to digest fibrin clots in vitro has been examined. In one assay, the lipid solutions were incubated with streptokinase, plasminogen activator or plasmin prior to addition of the lytic agent to the clot and its fibrinolytic activity was then assessed. Secondly, the lipids were incorporated into the clots and the three lytic agents were added directly. The lipids used markedly inhibited the lytic effect of plasminogen activator (34% mean) and plasmin (28.9% mean) when they were allowed to interact in solution prior to addition to the clot. Streptokinase was significantly inhibited in this manner but to a much smaller degree (7% mean). Lipids incorporated within the clots actually enhanced the lytic action of plasminogen activator (8.8% mean), mildly inhibited clot dissolution by plasmin (5.9%) and insignificantly altered the action of streptokinase. The effects of the lipids used appeared to be relatively nonspecific.